2016
DOI: 10.3892/etm.2016.3856
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-351 inhibits denervation-induced muscle atrophy by targeting TRAF6

Abstract: Abstract. MicroRNAs (miRs) have been observed to be involved in the modulation of various physiopathological processes. However, the impacts of miRNAs on muscle atrophy have not been fully investigated. In the present study, the results demonstrated that miR-351 was differentially expressed in the tibialis anterior (TA) muscle at various times following sciatic nerve transection, and the time-dependent expression profile of miR-351 was inversely correlated with that of tumor necrosis factor receptor-associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 28 publications
3
22
1
Order By: Relevance
“…However, in this study, miR-146a was significantly upregulated by Omp25 or WT B. suis infection in both PAMs and mouse RAW264.7 cells, which suppresses the transcription of TNF-α via targeting TRAF6 and IRAK1. Beside miR-146a, miR-351-5p has also been reported to target TRAF6 to inhibit denervation-induced muscle atrophy ( 41 ). In our work, miR-351-5p was found to be upregulated by Omp25 in RAW264.7 cells to inhibit TNF-α transcription via targeting TRAF6 and IRAK1, yet in PAMs miR-351-5p was not upregulated by Omp25 to regulate TRAF6 and IRAK1.…”
Section: Discussionmentioning
confidence: 99%
“…However, in this study, miR-146a was significantly upregulated by Omp25 or WT B. suis infection in both PAMs and mouse RAW264.7 cells, which suppresses the transcription of TNF-α via targeting TRAF6 and IRAK1. Beside miR-146a, miR-351-5p has also been reported to target TRAF6 to inhibit denervation-induced muscle atrophy ( 41 ). In our work, miR-351-5p was found to be upregulated by Omp25 in RAW264.7 cells to inhibit TNF-α transcription via targeting TRAF6 and IRAK1, yet in PAMs miR-351-5p was not upregulated by Omp25 to regulate TRAF6 and IRAK1.…”
Section: Discussionmentioning
confidence: 99%
“…As early as 2001, two pioneering studies reported that MuRF1 and MAFbx genes were similarly altered in disparate muscle atrophy conditions (Bodine et al, 2001 ; Gomes et al, 2001 ). Among a number of later works, our observations showed that skeletal denervation- or drug-induced skeletal muscle atrophy led to significant up-regulation of MuRF1 and MAFbx (Sun et al, 2014a , b ; He et al, 2016 ), while other researchers found that MuRF1 and MAFbx were up-regulated in skeletal muscle atrophy associated with cancer cachexia and cerebral ischemia (Gomes et al, 2012 ; Desgeorges et al, 2015 ; Winbanks et al, 2016 ).…”
Section: Introductionmentioning
confidence: 86%
“…Briefly, each animal was anesthetized by an intraperitoneal injection of complex narcotics, and the sciatic nerve was exposed through an incision on the lateral aspect of the mid-thigh of the left hind limb. A 1 cm long segment of sciatic nerve was then resected at the site just proximal to the division of tibial and common peroneal nerves, and the incision sites were then closed (Li et al, 2013 ; He et al, 2016 ). Then these animals were performed with daily intraperitoneal injection of saline, PQQ (5 mg/kg) in saline, or NAC (100 mg/Kg) in saline, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…MyomiRs, a class of miRNAs exclusively expressed or enriched in striated muscle, have been identified as essential determinants in regulatory networks of myogenesis, muscle fibre‐type composition, muscle growth, and homeostasis . Several miRNAs have also been shown to play a role in different experimental models of skeletal muscle atrophy, including miR‐18a, miR‐23a, miR‐27a, miR‐29b, miR‐351, miR‐422a, miR‐424(322)‐5p, miR‐542‐5p, and miR‐675 . AtromiRs have been dubbed as a collective term referring to miRNAs putatively involved in muscle atrophy, regulating processes and signalling pathways that contribute to muscle wasting .…”
Section: Introductionmentioning
confidence: 99%